(untitled) (Fiep Bulletin - online, 2012)
The Climacteric and menopause are part of the experience of one phase of life of women, silenced, permeated with prejudices, taboos, with demonstrations of physical, psycho-emotional and social. This study aimed to identify the meanings attributed to menopause for women who experience this experience. We used a qualitative approach in the phenomenological perspective. Participants 12 women aged between 45 and 60 users of the Basic Health Unit New Cross, located in the district Cruise in Campina Grande - PB in the period from May to October 2010. The results show that the woman experiences the menopause with unpleasant symptoms that change their daily life: decreased libido, loss of reproductive capacity, denial of sexuality and the beginning of the aging process. It is considered that postmenopausal women are in inauthenticity, dominated by talk, curiosity and ambiguity, and lead to the authenticity, opening up to new possibilities, free of menses, with availability of care and time to be able to develop new relationships for the achievement of a better life.